Developing a Peer Assisted Substance Abuse Program for Early Adolescents - Bourgeois, Robert M. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
Alcohol and drug abuse were viewed as a clear way of demonstrating personal or social sophistication in a Canadian secondary school. Neither the school nor the local community had developed a strategy for dealing with the problem of substance abuse among the students. The program described in this report was designed to reduce the level of alcohol and drug abuse among these early adolescents. The major objectives were to foster a greater sense of personal causation in the lives of the students; to teach specific decision-making skills; to develop student-created models for healthy lifestyles; and to have students identify a personal reduction in substance abuse as a result of participation in the program. Needs assessment surveys were developed and administered to students and to the school's Peer Helpers. Results were analyzed and possible solutions were examined. Among the proposed solutions was the use of a multi-faceted approach which took into account the needs of the individual adolescent, the peer group, and the family. The solution chosen utilized strategies designed to increase the self-esteem and sense of personal control of each participant. Results of the program were mixed. Analysis of the data showed that a large number of participants surveyed reduced their personal level of alcohol and drug use, but not as many as expected. (Author/ABL)
ERIC Note: Ed.D. Nova University. Appendixes contain some semilegible/illegible material.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adolescents; Alcohol Abuse; Alcohol Education; Decision Making Skills; Drug Abuse; Drug Education; Foreign Countries; Peer Influence; Prevention; Program Effectiveness; Secondary Education; Secondary School Students; Self Esteem; Substance Abuse; Early Adolescents; Canada; Dissertations/Theses, Practicum Papers; Reports, Descriptive; Reports, Evaluative